Study on prevalence and severity of urogenital complaints in postmenopausal women at a tertiary care hospital - Nidhi Gupta; Manju Aggarwal; Renuka Sinha; Neha Varun (Wolters Kluwer Medknow Publications, 2018)
Objective: The objective of this study was (1) to find the prevalence of urogenital (UG) complaints after menopause, (2) to evaluate the various risk factors for UG problems in postmenopausal women, and (3) to assess the severity of the symptoms depending on the duration of menopause. Materials and Methods: This study is a prospective study conducted at the Specialty Outpatient Department in Safdarjung Hospital over a period of 1 year. Two hundred postmenopausal women during this period were screened for UG complaints by eliciting detailed history in a pro forma and were divided into two groups based on the duration of menopause. Women with preexisting complaints before menopause and those with some medical disorders such as diabetes, stroke, or neurological problems were excluded from the study. Data were analyzed by standard statistical analytical tests. Results: The prevalence of UG symptoms in our study was 67%. Group A constitutes 127 (63.5%) participants in which menopause attained was of 1-5-year duration. Group B comprises the women with >5-year duration of menopause and it includes 73 (36.5%) patients. Among the genital complaints, vaginal dryness was the most common complaint in both the groups (Group A: 62% and Group B: 48%) followed by vaginal discharge or infection (Group A: 28% and Group B: 25%). Around 19 (15%) in Group A and 10 (13.6%) in Group B were having burning micturition (dysuria), the most common complaint encountered. The UG complaints were not statistically significantly different in both the groups. The severity of the symptoms was significantly different in two groups with more severe complaints in Group A as compared to Group B. Conclusion: UG complaints associated with estrogen loss can occur episodically throughout a women's life, but it is most common and chronic in the duration in postmenopausal women.